The Relationship of Knowledge of Pregnant Women to Compliance with Health Protocols During the Covid-19 Pandemic at the Kassi-Kassi Health Center Makassar in 2021 - rahman, Nur indah noviyanti; Hukmiyah Aspar; Gusriani (International Journal of Science, Technology & Management, 2021)
Relationship of Knowledge of Pregnant Women to Compliance with Health Protocols during the COVID-19 Pandemic at Kassi-Kassi Health Center Makassar in 2021. The purpose of this study was to determine the relationship between knowledge of pregnant women and adherence to health protocols during the COVID-19 pandemic at the Kassi-Kassi Health Center Makassar. This study uses analytical research methods by carrying out a Cross Sectional Study approach to determine the relationship between knowledge of pregnant women and adherence to health protocols during the COVID-19 Pandemic at the Kassi-Kassi Health Center Makassar. With a population of pregnant women who perform ANC examinations at the Kassi-Kassi Health Center Makassar and the number of samples is 30 respondents using the Accidental Sampling technique. From the results of statistical tests using the Chi-Square (Continuity Correction) test, the value of (0.039) < (0.050) is obtained, so Ha is accepted and H0 is rejected, this study shows that there is a relationship between knowledge of pregnant women and adherence to health protocols.